Aplication of growth hormone genes familly (GH, GHR, GHRH and Pit-1) for detecting genetic variation of buffaloes in Pandeglang and Lebak districts in Banten Province - Cece Sumantri; R Diyono; A Farajallah; A Anggraeni; E Andreas (Jurnal Ilmu Ternak dan Veteriner, 2010)
Selection using genetic markers are commonly performed to improve livestock productivity in the livestock industry. The objectives of this study were to identify growth hormone genes family (GH|MspI, GH|AluI, GHR|AluI, GHRH|HaeIII and Pit-1|HinfI) polymorphisms of Banten buffalo population consisted of Pandeglang and Lebak subpopulations. A total number of 209 blood samples were collected from 15 districts. Genomic DNAs were extracted by a standard phenol-chloroform protocol and amplified by a polymerase chain reaction (PCR) techniques, then PCR products of GH, GHR, GHRH and Pit-1 Genes were digested with MspI, AluI, HaeIII and HinfI enzyme restriction. Fragments of GH|MspI, GH|AluI, GHR|AluI, GHRH|HaeIII and Pit-1|HinfI were detected by EtBr method. The results showed that GH|MspI and GHRH|HaeIII loci were polymorphic, GH|AluI, GHR|AluI and Pit-1|HinfI, loci were monomorphic. GH allele (-) at locus GH|MspI was only found in Cisata (0.03) and Menes (0.11). Allele B at locus GHRH|HaeIII only found in Cibadak (0.42), Cisata (0.30) and Menes (0.11). In the total population of Banten locus GH|MspI have low diversity (He = 0.02) and polymorphic information content (Pic = 0.02), whereas GHRH|HaeIII locus has a higher diversity (He = 0.23) and Pic (0.22). Key Words: Polymorphism, Growth Hormone Genes, Buffalo